The impact of climate change on food security in ward 8 of Chivi district - Bere, Donald (Midlands State University, 2020)
The purpose of this study was to improve the brand image and perception of studying music courses. The research was qualitative in nature which encouraged the researcher to carry out an Action Research in the department of Music Business, Musicology and Technology in quest to improve the brand image and perception of studying music courses. The study identified the different perceptions the public have towards studying BSc Music Business, Musicology and Technology Honours degree at Midlands State University. As a course of action the study then implemented a magazine entitled, “Chit Chat” to showcase the nature of this degree program and the various activities which are done in the department. This was so done to; showcase the different musical activities which are done in the Music Business, Musicology and Technology department so as to enlighten the public on what really goes on this department. The study was informed by the brand personality theory, bullet theory and the communication model. Being qualitative in nature, the study utilised face-face in-depth interviews, questionnaires and participation observation guides to gather information. Participants were drawn from the population using purposive sampling and stratified random sampling. The feedback from the public after publishing the magazine was positive, meaning that, marketing music using the print media is an important aspect to implement in music education.